Improving DC coding models of JPEG arithmetic coder - Lakhani, G. (IEEE signal processing letters, 2004)
While conducting experiments with JPEG binary arithmetic coding, we noticed that if a natural photographic image is rotated by 90/spl deg/ and then coded, the DC code size is reduced in general. This led us to investigate the discrete cosine transform and statistical models of JPEG arithmetic coder, and formulate two modifications to DC coefficient coding. We propose that the DC of a block should be predicted from the block just above. This modification reduces the DC code size further by about 9% on average. This change is more important for arithmetic coding than Huffman DC coding. We also propose a change in the binary decision coding order specified by the DC statistical model; it produces only a minor reduction in the code size.